Analisis Kinerja Keuangan Sebelum dan Sesudah Akuisisi Pada Perusahaan PT Merdeka Copper Gold - Rosyta Pratiwi; Isna Khoirinnisa; Endang Kartini Panggiarti (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2023)
Changes in the company's financial performance before and after the acquisition were assessed using financial ratios, namely liquidity ratios (Current Ratio and Net Working Capital to Total Assets), leverage ratios (Debt to Total Assets Ratio and Debt to Total Equity Ratio) and profitability ratios ( Return On Assets and Return On Equity). This type of research is a quantitative research studied in a case study. The data source used is secondary data taken from the official website of PT Merdeka Copper Gold https://merdekacoppergold.com/, namely the financial statements before the 2017-2018 acquisition and after the 2020-2021 acquisition. The results of this study are that the liquidity ratio has increased after the acquisition, the leverage ratio has decreased after the acquisition and the profitability ratio has also decreased after the acquisition company. This shows that PT Merdeka Copper Gold has a better financial performance after making an acquisition in terms of the liquidity ratio and leverage ratio, but if it is seen from the profitability ratio the financial performance of PT Merdeka Copper Gold has decreased after the acquisition.